Competência digital docente na visão da complexidade: um estudo sobre a formação continuada de professores de língua inglesa - Rafaela Carla Santos de Sousa (2023)
The digital age presents new ways of accessing information and communication, creating a growing demand for the education area to prepare citizens for these practices. In the context of foreign language teaching, the integration of digital technologies is even more relevant, as it has the potential to expand classroom space and facilitate work with oral and written production from/for different nations and cultures. This research examines, through the lenses of Complexity, the development of the digital competence of public school English teachers. This study considers that teacher digital competence (Falloon, 2020) is associated with conditions of emergence, such as redundancy, diversity, neighbor interactions, decentralized control and enabling constraints (Davis; Sumara, 2006). This investigation has a qualitative and interpretive approach, analyzing data generated from three instruments: initial questionnaire, interactions of a six-week continuous professional development online course and final questionnaire. The findings show large contextual differences within the public education system in relation to the interaction between teachers, physical and organizational structures and the encouragement of teacher development. Teachers are part of a complex system composed of agents who need to share a coherent vision of the teaching and learning process, its objectives and possible paths. It is necessary to know and analyze the perspective of these agents, so that emergency conditions for digital teaching competence can be promoted.